KESIAPAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DALAM MENGIMPLEMENTASIKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH (SAKEMKM) UNTUK MENINGKATKAN AKSES MODAL PERBANKAN DAN LEMBAGA LAIN DI KOTA MALANG - Rani Laksmi Devindasari ; Dra. Wiwik Hidajah Ekowati, M.Si., Ak., CA (Akuntansi FEB - UB, 2018)
This research aims to examine information on accounting records held by micro, small, and medium enterprises (MSMEs) in the City of Malang and their readiness to implement the Financial Accounting Standards of Micro, Small, and Medium Enterprises (SAK-EMKM) to enhance their access to capital from banks and other institutions. The objects of this research are MSMEs in the City of Malang. The descriptive approach was used for this research. This research used the interview method and 32 interviewees were successfully interviewed. The results of this research indicated that 71.875% of MSMEs used simple accounting records, 9.375% had implemented financial accounting standards in their financial statements, and 18.75% had not yet prepared accounting records. The readiness of MSMEs to implement SAK-EMKM was assessed through three indicators: the knowledge of SAK-EMKM, separation between business and personal (owner’s) transactions, and human resources. The result of this research showed that 31 MSMEs did not yet have knowledge of SAK-EMKM, 18 MSMEs did not separate between business and personal (owner’s) transactions, and 30 MSMEs did not yet have enough human resources to keep accounting records based on SAK-EMKM. The conclusion of this research is that MSMEs are not yet ready to implement SAK-EMKM in their accounting records, though they are urged to implement SAK-EMKM to enhance their access to capital from banks and other institutions. Keywords: MSMEs, Financial Accounting Standards of Micro, Small, and Medium Enterprises (SAK-EMKM), readiness, access to capital from banks and other institutions